2019
DOI: 10.1016/j.actamat.2019.02.028
|View full text |Cite
|
Sign up to set email alerts
|

In situ investigation of stress-induced martensitic transformation in granular shape memory ceramic packings

Abstract: a b s t r a c tStress-induced martensitic transformation can occur in granular shape memory materials when individual particles experience high stresses and transform from a high-symmetry austenite phase to a lowsymmetry martensite phase. This involves a highly heterogeneous distribution of the driving force and very low mechanical constraint for martensite nucleation, so the transformation behavior can be dramatically different from the well-documented case of monolithic solids. In this work, we investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In a related study, similar microparticles were shown to exhibit cyclic superelasticity over hundreds of cycles with a maximum of 502 cycles probed (19). Subsequent work on open cell foams (20) and granular packings (21,22) demonstrated extension of shape memory properties to larger length scales by assembly of those smaller particles into larger structures. Notably, the open cell foam structures studied by Zhao et al (20) exhibited a thermally activated recoverable strain of 2% and stress induced transformation without fracture.…”
Section: Author Manuscriptmentioning
confidence: 94%
“…In a related study, similar microparticles were shown to exhibit cyclic superelasticity over hundreds of cycles with a maximum of 502 cycles probed (19). Subsequent work on open cell foams (20) and granular packings (21,22) demonstrated extension of shape memory properties to larger length scales by assembly of those smaller particles into larger structures. Notably, the open cell foam structures studied by Zhao et al (20) exhibited a thermally activated recoverable strain of 2% and stress induced transformation without fracture.…”
Section: Author Manuscriptmentioning
confidence: 94%
“…In the past decade, the brittle nature of ZrO 2 has been mitigated by constructing miniature specimens (e.g., micro-/nano-pillars 8 , single/oligo-crystals 9 12 , nano-fibers 13 , 14 ), and structures formed thereof (e.g., honeycombs via 3D printing 15 , cellular foams via freeze casting 16 , 17 , and granular packings 3 , 18 ), where the ceramic is relatively free to expand/contract because of the high specific surface area and/or the removal of grain boundaries. Nevertheless, it remains a challenge to integrate these small-volume shape memory ceramics into a matrix material and realize their reversible phase transformation in a confined state without causing fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The tetragonal (t) to monoclinic (m) martensitic transformation toughening, combing with high strength, superior corrosion resistance, and low thermal conductivity have made zirconia-based ceramics highly attractive for applications in biomedicine implant fabrication, the chemical industry, shape-memory, and thermal barrier coatings. [1][2][3] The martensitic transformation is reversible and always accompanied with a volume expansion or contraction of ∼4%, which leads to micro-cracks and degradation. 4 Although zirconia is generally alloyed with other oxides, such as Y 2 O 3 and CeO 2 , to obtain the fully tetragonal phase, the transformation can also be triggered by lowtemperature treatments within steam.…”
Section: Introductionmentioning
confidence: 99%